DEGRADASI SERAPAN AKSARA ARAB DAN MELEMAHNYA PENGARUH ISLAM: ANALISIS HISTORIS TERHADAP AKSARA ALJAMIADO, XIAOJING, DAN JAWI - Roslan Bin Ab Rahman; Riadussolihin Riadussolihin; Lenny Herlina (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
The Aljamiado, Xiaojing, and Jawi scripts are a manifestation of the acculturation of Arabic Islamic culture with the culture of various community groups spread across various parts of the world.  Acculturation is created through social interactions involving the carriers and disseminators of Islam.  The script adopted from Arabic grew along with the development of Islamic civilization, and weakened as Islamic civilization declined.  There have not been many studies on historical analysis and social construction by making comparisons between languages ??that adopt the Arabic script.  Most studies only focus on one character through various approaches.  This article aims to discuss the degradation of Arabic script absorption in Chinese, Spanish and Malay and reveal the essence behind its connection to the weakening influence of Islam.  This research uses a qualitative approach with the library research method.  Primary data sources include books and journals of previous research and other relevant sources.  The results of this research show that the degradation of the absorption of Arabic script in the form of Aljamiado, Xiaojing, and Jawi is directly proportional to the weakening of Islamic influence.  Meanwhile, its emergence was initiated by immigrant Muslims, driven by different conditions.  Aljamiado and Xiaojing were born as a result of weakening Islamic hegemony, while Jawi was born because Islamic influence was getting stronger